1998
DOI: 10.1049/pbcs010e
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Feedback Semiconductor Lasers

Abstract: lengths in space and time-central-difference method 7.3.3 Numerical stability 7.3.4 Gain and phase 7.4 Coupled reflections 7.4.1 Kappa coupling but no gain or phase changes 7.4.2 Matrix formulation 7.4.3 Phase jumps replacing scattering 7.4.4 Fourier checks 7.5 A uniform Bragg laser: finite difference in time and space 7.5.1 Full coupled-wave equations 7.5.2. MATLAB code 7.5.3 Analytic against numeric solutions 7.6 Spontaneous emission and random fields 226 7.6.1 Spontaneous noise and travelling fields 226 7.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(126 citation statements)
references
References 0 publications
1
120
0
2
Order By: Relevance
“…... general, but here we focus on the single-mode case where only one of them is relevant, which can be achieved using distributed Bragg gratings (DBG) [22] or periodic PT symmetric structures [17]. In Eq.…”
Section: Analytical Results: Supermode Coupled Equations For Susy Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…... general, but here we focus on the single-mode case where only one of them is relevant, which can be achieved using distributed Bragg gratings (DBG) [22] or periodic PT symmetric structures [17]. In Eq.…”
Section: Analytical Results: Supermode Coupled Equations For Susy Arraysmentioning
confidence: 99%
“…However, it was shown that their operation is dominated by multimode chaotic emission [19]. In general, the longitudinal modes associated with each cavity can be eliminated by using distributed Bragg gratings (DBG) [22] or periodic PT symmetric structures [17]. On the other hand, eliminating the transverse collective modes of the array is a daunting job.…”
Section: Introductionmentioning
confidence: 99%
“…Its contribution to the optical field is harmonically oscillating and dominates beyond threshold, giving rise to high coherence. Distributed feedback (DFB) semiconductor lasers come close to this ideal [CWP98]. They exhibit continuous wave (CW) single mode emission up to high pump currents.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled mode equations are used to model laser mode in the device [11] [14]. The electric field in the device is presented as: …”
Section: Mathematical Model and Simulation Parametersmentioning
confidence: 99%